Climate change and persistent high temperatures: does it matter? - Aral, Mustafa M. (Frontiers in Environmental Science, 2014)
Climate change may affect the behavior of various systems on earth, one of which is human population. In the current literature, it is hypothesized that anthropogenic impacts on earth may yield persistent and adverse climatic conditions which may become the norm rather than an exception. Given these climatic conditions, the world population may lose its stability and these climate conditions may trigger population shifts that may be characterized by regional migration patterns or loss of population. In this commentary the purpose is to review historical views on this subject and apply a mathematical model developed to provide computational insight to human population behavior given climatic conditions that are hypothesized to occur during the next millennium. The scenarios used for this purpose is hypothetical, but they may reveal critical population dynamics which may need to be taken into consideration in addressing future climate change impacts.